Three-Dimensional Simulation of The Water Flow in Cilacap’s Water, Indonesia - N. O. E. Froditus; D. G. Pratomo; C. B. Pribadi (Institut Teknologi Sepuluh Nopember, 2019)
Modelling of the water flow distribution in Cilacap’s water, Indonesia is challenged by geographically properties. This area is a strait adjacent to Indian Ocean with a strong current flow characteristic. A three‐dimensional model has been developed to understand the pattern of the flow and the sediment distribution in this waters. The parameters used in modeling includes hydro-oceanography, such as tidal, river discharge, bathymetry and sediment. River discharge that used came from Donan and Yasa River. In this research current and sediments model will be makes using numerical simulation with hydrodynamics equations. Based on the hydrodynamic simulation, at the spring tide period, the average and the maximum current magnitude are 0.6m/s and 0.8m/s respectively. But at this time the cumulative erosion/sedimentation is not too large. During the neap tide, the average current magnitude is 0.2 m/s and the sediment is moving significant at river. So in this time experience a great erosion/sedimentation. The dominant type of sediment in this waters is a type of sand. The sediment deposition in this area affects the shipping lane, particularly in the vicinity of the jetty.